2004
DOI: 10.1111/j.1524-4725.2004.30102.x
|View full text |Cite
|
Sign up to set email alerts
|

Single-Blind, Randomized Study Comparing Chromated Glycerin, Polidocanol Solution, and Polidocanol Foam for Treatment of Telangiectatic Leg Veins

Abstract: This study shows that CG is superior to POL solution and foam for sclerotherapy of leg telangiectasias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 9 publications
0
69
0
2
Order By: Relevance
“…Foam sclerosant is applied for the conventional treatment of varicose veins in the lower extremities [35,36]. Foam sclerotherapy using the detergent polidocanol is well known for its safety and efficacy in varicose vein treatment [37][38][39]. Breu and Guggenbichler [40] reported that the larger the diameter of the vein, the more viscous the foam should be to obtain better results.…”
Section: Discussionmentioning
confidence: 99%
“…Foam sclerosant is applied for the conventional treatment of varicose veins in the lower extremities [35,36]. Foam sclerotherapy using the detergent polidocanol is well known for its safety and efficacy in varicose vein treatment [37][38][39]. Breu and Guggenbichler [40] reported that the larger the diameter of the vein, the more viscous the foam should be to obtain better results.…”
Section: Discussionmentioning
confidence: 99%
“…The great advantages of foam over liquid sclerosant are a more uniform distribution on the endothelial surface and a prolonged local permanence time, enhancing the endothelial damage [33,34]. The main complication related to the foam is its intracardiac migration, with a possibility of cerebral embolization (in the presence of a right-to-left shunt) and neurological symptoms [35]. …”
Section: Discussionmentioning
confidence: 99%
“…4,6,7,[9][10][11][12][13][14][15][16] Patients of all abnormal, clinical, CEAP classes have been treated with UGFS. 1,2,4,6,7,[11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27][28] Foam sclerotherapy has been used to successfully treat: (1) saphenous veins primarily, (2) to complement, complete, or extend stripping or thermal ablation by laser or radiofrequency, (3) recurrent veins, (4) venous malformations, (5) venous aneurysms, (6) sciatic nerve varices, and (7) saphenous or nonsaphenous perforating veins. Side effects and adverse events have been described not only for UGFS but for all methods of treating the superficial veins of the lower extremity, surgical or nonsurgical.…”
mentioning
confidence: 99%